2012
DOI: 10.4141/cjss2011-028
|View full text |Cite
|
Sign up to set email alerts
|

Proposed classification for human modified soils in Canada: Anthroposolic order

Abstract: Naeth, M. A., Archibald, H. A., Nemirsky, C. L., Leskiw, L. A., Brierley, J. A., Bock, M. D., VandenBygaart, A. J. and Chanasyk, D. S. 2012. Proposed classification for human modified soils in Canada: Anthroposolic order. Can. J. Soil Sci. 92: 7–18. With increasing anthropogenic activity, the areal extent of disturbed soils is becoming larger and disturbances more intense. Regulatory frameworks must incorporate reclamation criteria for these disturbed soils, requiring consistent descriptions and interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A few studies have been conducted to use these waste materials to build soils, also known as anthroposols, for reclamation. Anthroposols are soils that have been altered by human activity; they include soils that are built for reclamation using various materials such as organic wastes (Naeth et al 2012). Research found that waste materials mixed with organic and inorganic amendments differed in their effects on vegetation, and those effects changed over time Naeth 2005a, 2005b;Drozdowski et al 2012;Naeth and Wilkinson 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have been conducted to use these waste materials to build soils, also known as anthroposols, for reclamation. Anthroposols are soils that have been altered by human activity; they include soils that are built for reclamation using various materials such as organic wastes (Naeth et al 2012). Research found that waste materials mixed with organic and inorganic amendments differed in their effects on vegetation, and those effects changed over time Naeth 2005a, 2005b;Drozdowski et al 2012;Naeth and Wilkinson 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Through agricultural land use, humans are accelerating soil formation and transformation to a depth of 100 cm or more (Veenstra and Burras 2015). In addition, the proposed Anthroposolic order for CSSC is based on humancaused disturbances to soils, and these soils can occur on agricultural landscapes if the disturbance goes beyond typical tillage that can be accounted for with the "p" suffix in the CSSC (Naeth et al 2012). Therefore, the increasing effect of humans on soil genesis over time suggests that classifying soil LFH horizons based on human-caused management practices (e.g., agriculture) is justified.…”
Section: Classifying Lfh Soil Horizons Based On Managementmentioning
confidence: 99%